2018
DOI: 10.1039/c8ob00627j
|View full text |Cite
|
Sign up to set email alerts
|

An improved synthesis of pyrido[2,3-d]pyrimidin-4(1H)-ones and their antimicrobial activity

Abstract: The screening of a small library of diverse chemical structures resulted in the identification of 2-thioxodihydropyrido[2,3-d]pyrimidine 10a as having broad spectrum antibacterial activity (MIC 0.49-3.9 μg mL-1), and reasonable antifungal activity (MIC 31.25 μg mL-1). An expeditious synthesis of 10a was optimized by varying solvents, catalysts and the use of microwave irradiation with the best conditions using DMF as a solvent, I2 (10 mol%) and a 30 minutes reaction time compared to 15 h for classic convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Synthesis of 7-Amino-3-phenyl [1,2,4]triazolo [4,3-a]pyrimidin-5(1H)-one (57). Fares et al 87 reported that some of the synthesized pyrido [2,3-d]pyrimidine derivatives displayed antimicrobial and anti-fungal activities. Among the tested derivatives, compound 63 (R 1 = 4-Cl-C6H4, R 2 = C6H5) was found to exhibit the most potent effect against Streptococcus pneumoniae and Escherichia coli.…”
Section: Table 8 Synthesis Of Compounds 54a-lmentioning
confidence: 99%
“…Synthesis of 7-Amino-3-phenyl [1,2,4]triazolo [4,3-a]pyrimidin-5(1H)-one (57). Fares et al 87 reported that some of the synthesized pyrido [2,3-d]pyrimidine derivatives displayed antimicrobial and anti-fungal activities. Among the tested derivatives, compound 63 (R 1 = 4-Cl-C6H4, R 2 = C6H5) was found to exhibit the most potent effect against Streptococcus pneumoniae and Escherichia coli.…”
Section: Table 8 Synthesis Of Compounds 54a-lmentioning
confidence: 99%
“…The antimicrobial action of compound 30a had shown MIC = 0.49-7.81 μg/ml and discrimination index was more than the normal against CCD-33Co cell line. Further, the antifungal action of derivatives 31a, 31b and 31c were found moderate to strong (Fares et al, 2018). Naeimi and co-workers synthesized an effective and appropriate pyrido [2,3-d: 6,5-d′] dipyrimidine derivatives through simple one pot, multicomponent reaction protocol of 2-thiobarbiturate, ammonium acetate and substituted aromatic aldehyde by condensation in the presence of [H-NMP] + [HSO 4 ] − as a catalyst.…”
Section: Anti-infectious Agentsmentioning
confidence: 99%
“…In the current situation, several heterocycles have emerged presenting a vital role in many medicinal agents, which have a direct impact on the health of mankind. Among these, pyrimidine turned to play a vital role in a broad range of pharmacological potential like anticancer, [ 2 ] antimicrobial, [ 3–5 ] antiinflammatory, antiviral, [ 6 ] anxiolytic, and anticonvulsant. It is an aromatic heterocycle comprising two nitrogen atoms at the first and third positions and four carbon atoms.…”
Section: Introductionmentioning
confidence: 99%